Integrative and complementary practices in primary care: Integrative literature review (Research, Society and Development, 2021)
Integrative and complementary practices seek to encourage the use of natural ways to prevent diseases, promote, maintain and recover health, through safe and effective practices. These systems emphasize the welcoming way of listening, the formation of a therapist-patient bond and the person's integral attention to society and the environment. The general objective of this study was to analyze the scenario of scientific production on integrative and complementary practices with an emphasis on primary health care. This is an exploratory literature review in the following databases: Scientific Electronic Library Online (SciELO) and Virtual Health Library (VHL). Data collection took place from January to March 2019. 148 scientific studies were found, 101 in the BVS database and 47 in SciELO. After reading, those who met the research objectives were selected. It was found that the largest number of publications according to geographic region comes from the southeast, northeast and south. Three thematic categories emerged on topics covered in the studies: PICS implementation process in primary care, application of PICs for various purposes in the context of primary care and training/training of health professionals involved. It was concluded, through the studies considered here, a scenario in which PICs are increasingly being the object of research, and this introduces us to the relevance of implementing this model of services in primary care.